Workplace Spirituality and Organizational Citizenship Behavior: A Mediating Role of Teachers’ Commitment - Maharjan, Minju; Pokhrel, Shree Krishna Pokhrel; Pokhrel, Laxman; Giri, Bishnu (Journal of Business and Management, 2024)
Background: Workplace spirituality is an emerging concept in Nepali academic institutions to promote a sense of meaningful work and interrelationship among teachers. It is considered a crucial factor in fostering employee positive workplace behavior. Objectives: This study aims to examine the mediating role of Teachers’ Commitment (TC) to Workplace Spirituality (WPS) and Organizational Citizenship Behavior (OCB) among Teachers of Management Colleges in the Kathmandu Valley. Methods: The study used a cross-sectional survey research approach to collect information from 250 teachers of Management College in the Kathmandu Valley. The respondents were contacted using the purposive sampling technique. Partial Least Squares Structural Equation (PLS-SEM) method was used to test the proposed hypotheses. Results: The findings reveal that Workplace Spirituality significantly affects Organizational Citizenship Behavior and Teachers’ Commitment. However, TC does not affect OCB. Furthermore, TC partially mediates the relationship between WPS and OCB. It suggests that WPS is a significant factor influencing OCB and TC among Kathmandu Valley management college teachers. Conclusion: This paper aids policymakers and college principals in improving WPS to create and support an OCB culture, ensure commitment, and increase effectiveness. Organizations can use the findings to develop a better workplace environment to enhance employees’ performance. JEL Classification: D23, J24, M12, M54